2016
DOI: 10.1016/s1473-3099(16)30007-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological data accessibility in Brazil

Abstract: PAHO. Neurological syndrome, congenital malformations, and Zika virus infection. Implications for public health in the Americas-Epidemiological Alert. 2015. http://www.paho. org/hq/index.php?option=com_content& view=category&layout=blog&id=1218&Item id=2291 (accessed Feb 13, 2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…There are many initiatives to make relevant data sources public, such as temperature and maps. However, the availability and accessibility of health data is still a challenge in Brazil [ 124 ] and worldwide [ 27 ]. Efforts that aim to use data from social networks [ 125 ], news, searches [ 126 , 127 , 128 , 129 , 130 ], crowdsourcing and volunteered geographic information [ 131 ] for modeling epidemics and health surveillance are interesting and show promising results.…”
Section: Discussionmentioning
confidence: 99%
“…There are many initiatives to make relevant data sources public, such as temperature and maps. However, the availability and accessibility of health data is still a challenge in Brazil [ 124 ] and worldwide [ 27 ]. Efforts that aim to use data from social networks [ 125 ], news, searches [ 126 , 127 , 128 , 129 , 130 ], crowdsourcing and volunteered geographic information [ 131 ] for modeling epidemics and health surveillance are interesting and show promising results.…”
Section: Discussionmentioning
confidence: 99%
“…System on Reportable Diseases (SINAN) for collecting and processing data on mandatory communicable diseases. [7] Event notification processes, however, are sensitive to incomplete and/or incorrect data, resulting in the inaccurate evaluation of epidemiological studies performed on these data. [8] A number of studies have reported difficulties in collecting reliable data for many communicable diseases, compromising its epidemiological monitoring.…”
Section: National Unified Public Health System (Sus) Including the Bmentioning
confidence: 99%
“…[5-6] In this context, Brazil has been employing information systems developed for its National Unified Public Health System (SUS), including the Brazilian National Information System on Reportable Diseases (SINAN) for collecting and processing data on mandatory communicable diseases. [7]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, finding epidemiological data interfaces or data within an interface is often a time-consuming and error-prone task. For example, the Zika virus epidemic has resulted in increased global attention for Brazil, but it has not resulted in a single easy-to-understand machine-readable interface [29]. Until just recently, Brazil's Ministry of Health maintained two separate lists of mosquito-borne illness epidemiological bulletins [30,31].…”
Section: Interface Challengesmentioning
confidence: 99%